North Saami - Luobbal Sámmol Sámmol Ánte; Ylikoski Jussi (Oxford University Press, 2023)
North Saami (known as “Norwegian Lappish” in older literature) is an indigenous language spoken by probably more than 25,000 people in Norway, Sweden, and Finland. North Saami today has an international standard form which is also used in literature, in the media, and in the education system, in areas with Saami majorities even in public and official interaction. Of the endangered Saami languages, North Saami is thus the most vigorous one; it also has a relatively strong research tradition. Taxonomically and geographically, North Saami is situated at the eastern end of the Western Saami subgroup. It is characterized by rich and complex phonology and morphophonology and considerable dialectal variation, which makes the relationship between the standard orthography and pronunciation very complicated. In this chapter, the main features of the structure, grammar, and lexicon of North Saami are briefly described. The chapter ends with a glossed text example.
The Oxford Guide to the Uralic Languages